EVALUATION OF SUBJECT-SPECIFIC MASTICATORY MUSCLE FORCE USING COMPUTATIONAL ANALYSIS - Fauziyyah Nursadida, Nada
Masticatory force is an important parameter to evaluate the efficacy of the masticatory system as it may be used to understand the mechanics of mastication as well as assess the functional performance of prosthodontic components. A number of measurement devices have been developed, but with several drawbacks, mastication force calculations are still disrupted which results in a less accurate value. The mastication movement occurs in transverse direction besides the vertical one so an analysis in a three-dimensional space is required. Evaluation of the masticatory muscle force is needed to enhance better understanding of mastication movement as the masticatory force actually results from the action of the jaw muscles modified by the craniomandibular biomechanics. This research replicates the framework developed by Röhrle O. et al., (2018) in evaluating masticatory forces through kinematic analysis using motion capture and occlusal load analysis using finite element simulation. The novelty aimed at by this research is the development of the framework by evaluating masticatory muscle forces using a musculoskeletal model that has been developed based on a specific subject. The developed framework was proved to be effective in estimating force exerted during mastication process. The use of finite element modeling minimizes the disruption from the previously developed device which results in an overestimated bite force. A further study of the musculoskeletal model of the masticatory system may be needed to enhance the study in masticatory system movement.